ALIRAN SEMPALAN DI KOTA BANJARMASIN (KAJIAN TERHADAP AJARAN ABAH PAL LIMA) - DAILY, ARNI (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2019)
The Sempalan sect taught by Abah Pal Lima has been developing for a long time, with a number of followers of more than seven thousand people scattered across different regions, and its teachings do not have a handbook. People are interested in this teaching because they have advantages such as alternative medicine and other magic powers. Throughout his teachings, he also believes in the presence of God, who has different qualities but does not believe in the foundations of faith and the pillars of Islam. So do not believe in the existence of gods, prophets, holy books (the Koran) as well as the question of taqdir, and there is no duty to worship and not to make prayers, fasting, zakat and pilgrimages. He assumed that besides him and his followers, they were considered heretics and would go to hell. This teaching gives priority to mental problems and believes that they are